PENGARUH FREKUENSI PENGENDALIAN GULMA TERHADAP POPULASI GULMA PADA TANAMAN BAWANG MERAH (Bima Brebes) - Rosita Wulandari; Encik Akhmad Syaifudin; Ni’matuljannah Akhsan (Agriculture Faculty, University of Kutai Kartanegara, Indonesia, 2021)
The purpose of this study was to find the best dosage of Trichokompos fertilizer which gives the best results on shallot plants and to determine the amount or frequency of weed control that affects shallot plants. Kutai Kartanegara Regency, East Kalimantan Province , since November 2019 until January 2020. The research used the Split Plot design 4x5 consisting of 2 factors and repeated 3 times. The First factor is Trichocompos fertilizer (t) consisting of 4 levels, namely (t0) No Fertilization, (t1) 2,5 kg plot-1, (t2) 3 kg plot-1, (t3) 3,5 kg plot-1. The second factor is weed control (g) consisting of 5 levels, namely (g0) without weed control, (g1) once a week equivalent to 8 times weed control, (g2) once a week equivalent to 4 times weed control, (g3) once a week equivalent to 3 times weed control, (g4) once a week equivalent to 2 times weed control. The results showed the effects of weed control on the number of leaves at the age of 40 and 60 dap, the number of tubers showed a significant effect. Plants that are free from weeds will show better growth when compared to those grown with 6.69 tubers of weeds. Then the lowest average result is the treatment of 5.36. Weed control also had a significant effect on weed populations and weed dry weight. It is suspected that there are weed seeds that are buried in the soil during the soil cultivation process causing the seeds to be lifted back to the surface of the soil during weed removal which causes new weeds to grow.